A cultura do Canto Coral no oeste catarinense (1920-1970) - Wolfarth, Márcia Luzia Freitag (2017)
This present research looked for to analyze the German culture in the west of Santa Catarina, to understand what way music served as a form of legitimation in the new homeland, don’t forgeting of german cultural origins, Analyze formation of singing societies created for the purpose of boasting their culture , the focus of this research facing to Orpheonic Singing at Santa Catarina’s west and their use as a form to nostalgia and german ethinic identity. Therefore, was elaborated reflective considerations regarding the Orpheonic Singing, that constitutes an extraordinary tool to establish a dense network of social and cultural configurations with the links of the valorization of the own individuality, the individuality of the other and the respect of interpersonal relationships, in a commitment of solidarity and cooperation. Orpheonic Singing is configured as an exercised musical practice and widespread in many different ethnicities and cultures. Through this research, I try to understand what was the importance of especially music Orpheonic Singing in identity construction process in Western Santa Catarina as first residents sought to represent their region of origin using music to reduce the miss, with some nostalgia. It is considered the choral project in light of the concept of creating a symbiology that allows the invention of regional identity as something that is renewed and constantly changes. This sing style was used in other counties with civic and patriot connotations and boosted in Brazil cause of Villa-Lobos performance during Vargas govern. The “New State” with a dominate characteristic and strict measures helps the obligation implatation of Orpheonic Sing at brazilian schools, considered the best local to nacionatlist actions, registering the intense prattice intended brazilian’s feelings. The students participation at singing and marching in parades and civic cerimonies also required by law’s force. In Santa Catarina a elevate number of imigrants that concentred at clonies scattered of many regions, that jutified a governament program in way to feed the brasilian’s feelings, through imposition of civicpatriotic songs. In southern Brazil after one Colonization wave groups with a view to strengthening social bonds mainly with people of the same ethnicity and religion, aiming to strengthen the friendship and solidarity ties of these groups have created associations that were canceled by the New state, Vargas government. Later they resurfaced as singing societies and understand the formation of the artistic and Cultural League of Western Santa Catarina and its role as cultural in the region.